2002
DOI: 10.1002/1521-3757(20020315)114:6<1078::aid-ange1078>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastable and Highly Acidic, Zeolite-Coated Mesoporous Aluminosilicates

Abstract: The acidity and hydrothermal stability of mesoporous aluminosilicates (MesoAS) are relatively low compared to those of zeolites, which limits their potential applications as catalysts in petroleum refining and fine chemicals synthesis. [1±7] Much effort has therefore been undertaken to synthesize a new type of materials, which combines the advantages of both zeolites and mesoporous molecular sieves. One might expect to improve both the stability and acidity of these materials if zeolite-like order could be in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Thus, as soon as crystallization of the mesopore walls occurs, the constraints often involve distortion and even collapse of the mesostructure. To avoid this phenomenon, several measures can be taken including using more stable mesoporous materials, that is, with thicker walls, such as SBA‐15,102, 115 using milder conditions like lower temperatures or other solvents, such as glycerol, to limit silica dissolution and moderate zeolite growth 103. 107, 116 An alternative is to fill the mesopores with an organic compound which, upon pyrolysis under nitrogen, will give a CMK‐type carbon material that maintains the mesostructure during the crystallization 117.…”
Section: Constructive Synthesis Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, as soon as crystallization of the mesopore walls occurs, the constraints often involve distortion and even collapse of the mesostructure. To avoid this phenomenon, several measures can be taken including using more stable mesoporous materials, that is, with thicker walls, such as SBA‐15,102, 115 using milder conditions like lower temperatures or other solvents, such as glycerol, to limit silica dissolution and moderate zeolite growth 103. 107, 116 An alternative is to fill the mesopores with an organic compound which, upon pyrolysis under nitrogen, will give a CMK‐type carbon material that maintains the mesostructure during the crystallization 117.…”
Section: Constructive Synthesis Strategiesmentioning
confidence: 99%
“…Another approach is based on the use of an amorphous mesoporous matrix as a support for zeolite precursors or nanocrystals. After impregnation of preformed mesoporous materials with zeolite seeds and treatment at high temperature, semicrystalline zeolitic mesopore walls are obtained 103. 105, 108, 109…”
Section: Constructive Synthesis Strategiesmentioning
confidence: 99%
“…While these methods perhaps show some derivation from early reports of the conversion of zeolites into mesostructures, or indeed vice versa, those early routes tended to result only in intimate mixtures of separate domains of the zeolite and the mesostructure. , Indeed, a more recent report suggested that pore-wall crystallization of mesoporous aluminosilicates can be achieved by using the mesostructure as the silicate source in a modified zeolite synthesis . Analysis of that data, however, strongly suggested that the mesostructure was simply being dissolved and subsequently recrystallized in situ, once again producing separate domains of mesostructure and zeolite.…”
Section: Introductionmentioning
confidence: 99%
“…An increase in surface area of about 56% was observed along with pore volume (30%) (figure 4). Ultra-stable mesostructured aluminosilicate with high acidic property using such primary zeolitic units of seed solution was reported to exert high stability attributed mainly to the presence of nanolayered zeolitic units at the mesopore walls of aluminosilicates [29]. Similar technique was used to synthesize different structured mesoporous molecular sieves involving MCM-48 with zeolite nanolayers (building units) [30].…”
Section: Thermogravimetric Analysismentioning
confidence: 99%